Semi-solid battery composite diaphragm and preparation method thereof

By coating functional coating slurry and inorganic solid -state electrolytes on the semi -solid battery septum, forming a composite septum, solving the problem of instability and mechanical stress of solid electrolyte and electrode material interface, significantly improved battery performance and safety Essence

CN119361976AInactive Publication Date: 2025-01-24HEFEI CHANGYANG NEW ENERGY TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411921550.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The interface between the solid electrolyte and the electrode material in a semi-solid state battery may cause instability, resulting in problems during the charging and discharging process, such as the increase in the interface impedance; at the same time, the diaphragm may face excessively large during the charging and discharging process. Mechanical stresses need to be improved to prevent cracks and deformation.

Method used

A composite septum composed of porous membrane, first coating, and second coating of thermoplastic resin, by coating the first coating and inorganic solid -state -containing first coating and inorganic solid state by coating the surface and lower surface of the porosity of the thermoplastic resin The second coating of the electrolyte forms a diaphragm with excellent tensile strength and pore rate.

Benefits of technology

A significant improvement of battery performance, enhanced the interface stability between solid electrolyte and electrode materials, improved the mechanical strength and ionic conductivity of the diaphragm, improved the interface contact with the electrode, further improved the electrochemical stability and safety of safety sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361976A_ABST
    Figure CN119361976A_ABST
Patent Text Reader

Abstract

The invention provides a composite diaphragm of a semi-solid-state battery and a preparation method thereof, and belongs to the technical field of diaphragms, the composite diaphragm of the solid-state battery comprises a thermoplastic resin porous base membrane, and a first coating and a second coating which are respectively coated on the upper surface and the lower surface of the thermoplastic resin porous base membrane; the preparation method of the semi-solid battery composite diaphragm comprises the following steps: coating two sides of the upper and lower surfaces of a thermoplastic resin porous base membrane with first coating slurry and second coating slurry on the upper and lower surfaces of the thermoplastic resin porous base membrane, baking to form a first coating and a second coating, and rolling to obtain the composite diaphragm, compared with a traditional semi-solid-state battery diaphragm, the solid-state battery composite diaphragm provided by the invention has the advantages that the interface stability between a solid-state electrolyte and an electrode material can be enhanced, and the diaphragm has excellent tensile strength and porosity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of diaphragms, and in particular to a semi-solid battery composite diaphragm and a preparation method thereof. Background Art

[0002] With the continuous miniaturization of electronic devices and the rapid development of mobile communication equipment, portable electronic information products, electric vehicles, and energy storage power stations, traditional lithium-ion batteries with transition metal oxides such as lithium cobalt oxide, lithium manganese oxide, and lithium nickel oxide as positive electrode materials can no longer meet the needs of overall development, especially the requirements of high specific capacity and high safety. Semi-solid batteries are batteries between liquid lithium-ion batteries and all-solid-state batteries. Their electrolytes are solid-liquid mixed states, and part of the liquid electrolyte is replaced by solid electrolytes or a large amount of solid substances are added to the liquid electrolyte to form a gel electrolyte. Compared with lithium-ion batteries, semi-solid batteries are expected to have higher energy density, reaching 300-500Wh / kg, while lithium-ion batteries are generally around 140-230Wh / kg; in terms of safety, semi-solid batteries reduce the content of liquid electrolytes due to the presence of solid electrolytes, reduce the risk of short circuits, and have higher thermal stability. Unlike lithium-ion batteries, they are prone to electrolyte leakage, fire and explosion under abnormal conditions such as overcharging, overheating, and short circuits. However, the interface between the solid electrolyte and the electrode material in the current semi-solid battery may be unstable, causing problems in the battery during charging and discharging, such as increased interface impedance; the diaphragm may face mechanical stress during charging and discharging, and its strength and flexibility need to be improved to prevent cracks and deformation. Those skilled in the art are in urgent need of developing a composite diaphragm for semi-solid batteries and a preparation method thereof to meet existing usage needs and performance requirements. Summary of the invention

[0003] In view of the above problems, the present invention aims to provide a composite diaphragm for a semi-solid battery and a preparation method thereof.

[0004] In order to solve the problem that the interface between the solid electrolyte and the electrode material of a semi-solid battery may be unstable and may face excessive mechanical stress during charging and discharging, the present invention provides a semi-solid battery composite diaphragm. Compared with the traditional semi-solid battery diaphragm, the present invention can enhance the interface stability between the solid electrolyte and the electrode material, and the diaphragm has excellent tensile strength and porosity.

[0005] The present invention is achieved through the following technical solutions: A semi-solid composite diaphragm is composed of a thermoplastic resin porous membrane, a first coating and a second coating. The thickness of the composite diaphragm is 24 to 34 μm; the preparation method of the semi-solid battery composite diaphragm comprises the following steps: coating the upper and lower surfaces of the thermoplastic resin porous base membrane with a first coating slurry containing a functional coating slurry and a second coating slurry containing an inorganic solid electrolyte on both sides of the upper and lower surfaces of the thermoplastic resin porous base membrane, baking to form the first coating and the second coating, and rolling up to obtain the composite diaphragm; the thickness of the first coating is 2 to 7 μm, and the thickness of the second coating is 2 to 7 μm.

[0006] Furthermore, the first coating slurry is prepared by the following method: by weight, 20 to 30 parts of functional coating slurry, 5 to 10 parts of binder, and 30 to 40 parts of water are stirred evenly to obtain the first coating slurry; the functional coating slurry comprises the following components in parts by weight: 5 to 10 parts of silica particles, 5 to 20 parts of polyvinyl alcohol, 10 to 15 parts of thickener, 8 to 10 parts of defoamer, 2 to 4 parts of dispersant and 65 parts of deionized water.

[0007] Furthermore, the preparation method of the functional coating slurry is as follows: (1) adding silica particles into deionized water, dispersing them using a high-speed stirrer, stirring until the particles are evenly dispersed, adding a dispersant and continuing to stir until stable, to obtain a pretreated inorganic particle slurry; (2) Adding polyvinyl alcohol to deionized water at a constant temperature of 80° C. while stirring to obtain a polyvinyl alcohol solution; (3) Add the pretreated inorganic particle slurry into the reactor, turn on the stirrer, and slowly add the polyvinyl alcohol solution. After the addition is completed, raise the temperature to 70°C, keep stirring, and control the coating reaction time to 5 hours; (4) Before the coating reaction is completed, add a defoamer and a thickener, stir evenly, and obtain a functional coating slurry.

[0008] Furthermore, the second coating slurry is prepared by the following method: 1-2 parts of dispersant are added to 8-10 parts of deionized water, and the mixture is stirred for 30 minutes, 15-20 parts of inorganic solid electrolyte are added, and the mixture is stirred for 40-60 minutes to obtain a water dispersion; 8-10 parts of coconut oil diethanolamide are added for thickening, and 50 parts of deionized water are added to obtain a deionized water dispersion, and the mixture is stirred for 2 hours, 3 parts of binder are added, and the mixture is stirred for 2 hours; finally, an inorganic solid electrolyte slurry, i.e., the second coating slurry, is prepared. After baking, a coating is formed, and the composite diaphragm of a semi-solid battery is obtained by rolling up.

[0009] Furthermore, the inorganic solid electrolyte is lithium lanthanum zirconium oxide or lithium zinc germanate.

[0010] Furthermore, the dispersant is one of TH-904, BYK-190 or sodium polyacrylate.

[0011] Furthermore, the thickener is coconut diethanolamide.

[0012] Furthermore, the thermoplastic resin porous base membrane is a PE diaphragm prepared from polyethylene raw materials.

[0013] Furthermore, the composite membrane has a thickness of 24 to 34 μm.

[0014] Furthermore, the baking temperature is 60-80° C. and the baking time is 1-2 hours.

[0015] Lithium lanthanum zirconium oxide garnet-type solid electrolyte, chemical formula Li7La3Zr2O 12 , referred to as LLZO.

[0016] Beneficial effects of the present invention: one layer of the semi-solid diaphragm is coated with a functional coating slurry, and the other layer is coated with a solid electrolyte material, which can significantly improve the battery performance. The polyvinyl alcohol coating not only enhances the mechanical strength of the diaphragm, but also improves the ionic conductivity, thereby improving the interface contact with the electrode. The coating of the solid electrolyte material further improves the electrochemical stability and safety, and reduces the occurrence of side reactions. On the whole, this design effectively improves the energy density and thermal safety of the battery and has good application prospects. Compared with the traditional method of coating PE diaphragms with inorganic materials, the present invention adopts a method of coating inorganic nanomaterials with polyvinyl alcohol and then coating. This innovation can significantly enhance the mechanical strength and toughness of the diaphragm, while improving the ionic conductivity and improving the interface contact with the electrode. In addition, the coating of the solid electrolyte material further improves the electrochemical stability and safety, and reduces the occurrence of side reactions. The invention can provide high-performance diaphragms for semi-solid batteries, meeting the demand for high-end diaphragms in multiple fields such as energy storage batteries, power batteries, and 3C digital products. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 TEM image of polyvinyl alcohol-coated silica particles; Figure 2 This is a schematic diagram of the structure of a semi-solid battery composite separator; Among them, 1 is a first coating layer, 2 is a second coating layer, and 3 is a porous base film of a thermoplastic resin. DETAILED DESCRIPTION

[0018] The present invention is described below with specific examples, but is not intended to be limiting of the present invention.

[0019] The following examples 1 to 3 use the following raw materials: TH-904 and BYK-190 from Shandong Taihe Technology Co., Ltd., spherical silica particles with a particle size of 200 nm from Anhui Fangxing Technology, LLZO inorganic solid electrolyte Ningbo Fengli New Energy LLZO-G3-300; Yiwu Zhongli Industry and Trade ZL057 high carbon alcohol defoamer; Shanghai Yuanye Biotechnology Co., Ltd. GY-738 coconut diethanolamide; Wanwei High-tech Materials 17-96 (L) polyvinyl alcohol; 8000rpm AIR-10S Shanghai Ouhe high-speed agitator; diaphragm coating binder 8501. Example 1

[0020] like Figure 2 As shown, the solid-state battery composite separator includes a thermoplastic resin porous base film 3 and a first coating layer 1 and a second coating layer 2 coated on the upper and lower surfaces of the thermoplastic resin porous base film respectively.

[0021] Step 1: Preparation of functional coating materials for coating inorganic particles: By weight, add 5 parts of silica particles to 20 parts of deionized water, and use an AIR-10S high-speed stirrer to disperse them. The stirring time is 1 hour to make the particles evenly dispersed. Add 2 parts of TH-904 dispersant and continue stirring for 20 minutes to allow the dispersant to fully adsorb on the surface of the inorganic particles. In another container, heat a certain amount of deionized water to 80°C. Slowly add 15 parts of polyvinyl alcohol, stirring while adding to prevent the polyvinyl alcohol from agglomerating. Continue stirring and maintain the temperature at 80°C to completely dissolve the polyvinyl alcohol to form a transparent 25wt% polyvinyl alcohol solution. Stir and dissolve for 3 hours at a stirring speed of 200rpm; add the pretreated inorganic particle slurry to the reactor. Turn on the stirrer and slowly add the obtained polyvinyl alcohol solution. Raise the temperature of the reactor to 70°C and keep stirring to allow the polyvinyl alcohol to coat the surface of the inorganic particles, such as Figure 1 As shown. The coating time is 5 hours. The average particle size of the polyvinyl alcohol-coated inorganic particles is 0.9 μm; when the coating time reaches 90% of the total coating time, that is, after coating for 4.5 hours, 10 parts of high-carbon alcohol defoamer and 15 parts of coconut oil diethanolamide thickener are added, stirred evenly, and finally a functional coating slurry of polyvinyl alcohol-coated inorganic particles is prepared.

[0022] Step 2: Preparation of first coating slurry: By weight, 25 parts of functional coating slurry, 8 parts of binder, and 35 parts of water were stirred evenly to obtain a first coating slurry. The functional coating slurry of the polyvinyl alcohol-coated inorganic particles was coated on one side of the base film. After baking at 80° C. for 1 hour, a first coating was formed, and the composite diaphragm was rolled up; the first coating had a thickness of 2 μm.

[0023] Step 3: Preparation of the second coating slurry: By weight, 1 part of TH-904 dispersant was added to 8 parts of deionized water, and stirred thoroughly for 30 minutes. 20 parts of LLZO inorganic solid electrolyte were added and stirred for 60 minutes to obtain a water dispersion. 8 parts of coconut oil diethanolamide were added for thickening, and 50 parts of deionized water dispersion were added and stirred for 2 hours. 3 parts of binder were added and stirred for 2 hours. Finally, an inorganic solid electrolyte slurry was prepared. After baking at 80°C for 1 hour, a second coating was formed, and the composite diaphragm of the semi-solid battery was rolled up. The thickness of the second coating was 5 μm. Example 2

[0024] The method is the same as that of Example 1, except that 10 parts of silicon dioxide particles, 20 parts of polyvinyl alcohol, and 4 parts of TH-904 dispersant are added. The solid-state battery composite separator includes a thermoplastic resin porous base film and a first coating layer of 7 μm and a second coating layer of 7 μm coated on the upper and lower surfaces of the thermoplastic resin porous base film, respectively. Example 3

[0025] The same method as Example 1 is used, except that 2 parts of silica particles, 5 parts of polyvinyl alcohol, and 2 parts of TH-904 dispersant are added, and the solid-state battery composite separator includes a thermoplastic resin porous base film and a first coating of 2 μm and a second coating of 2 μm respectively coated on the upper and lower surfaces of the thermoplastic resin porous base film. Example 4

[0026] TH-904 and BYK-190 from Shandong Taihe Technology Co., Ltd., 200nm spherical silica particles from Anhui Fangxing Technology, LLZO inorganic solid electrolyte from Ningbo Fengli New Energy LLZO-G3-300; ZL057 high carbon alcohol defoamer from Yiwu Zhongli Industry and Trade; GY-738 coconut oil diethanolamide from Shanghai Yuanye Biotechnology Co., Ltd.; 17-96 (L) polyvinyl alcohol from Wanwei High-tech Materials; 8000rpm AIR-10S Shanghai Ouhe high-speed agitator; 8501 diaphragm coating adhesive.

[0027] Step 1: Preparation of functional coating materials for coating inorganic particles: By weight, 5 parts of silica particles were added to 20 parts of deionized water, and the particles were dispersed using an AIR-10S high-speed stirrer for 1 hour to disperse the particles evenly. 2 parts of BYK-190 dispersant were added and stirred for 20 minutes to allow the dispersant to be fully adsorbed on the surface of the inorganic particles. In another container, a certain amount of deionized water was heated to 80°C. 15 parts of polyvinyl alcohol were slowly added, stirring while adding to prevent polyvinyl alcohol from agglomerating, and the temperature was continued to be stirred and maintained at 80°C to completely dissolve the polyvinyl alcohol to form a transparent 25wt% polyvinyl alcohol solution. The stirring and dissolving time was 3 hours and the stirring speed was 200rpm; the pretreated inorganic particle slurry was added to the reactor. Turn on the stirrer and slowly add the obtained polyvinyl alcohol solution. The temperature of the reactor was raised to 70°C and stirred to coat the surface of the inorganic particles with polyvinyl alcohol. The coating time was 5 hours. Among them, the mass ratio of silicon dioxide particles to polyvinyl alcohol is 1:3; the average particle size of the polyvinyl alcohol-coated inorganic particles is 0.9 μm; when the coating time reaches 90% of the total coating time, that is, after 4.5 hours of coating, 8 parts of high-carbon alcohol defoamer and 15 parts of coconut diethanolamide thickener auxiliary are added, stirred evenly, and finally a functional coating slurry of polyvinyl alcohol-coated inorganic particles is prepared.

[0028] Step 2: Preparation of first coating slurry: By weight, 20 parts of functional coating slurry, 5 parts of binder and 30 parts of water were stirred evenly to obtain the first coating slurry. The functional coating slurry of the polyvinyl alcohol-coated inorganic particles was coated on one side of the base film. After baking at 80°C for 1 hour, a coating was formed, and the composite diaphragm was rolled up; the coating thickness was 5 μm.

[0029] Step 3: Preparation of the second coating slurry: By weight, 2 parts of BYK-190 dispersant were added to 10 parts of deionized water, and stirred thoroughly for 30 minutes. 20 parts of LLZO inorganic solid electrolyte were added and stirred for 50 minutes to obtain a water dispersion. 10 parts of coconut oil diethanolamide were added for thickening, and 60 parts of the obtained water dispersion were added and stirred for 2 hours. 3 parts of binder were added and stirred for 2 hours. Finally, an inorganic solid electrolyte slurry was prepared. After baking at 60°C for 2 hours, a coating was formed, and the composite diaphragm of a semi-solid battery was rolled up. The coating thickness was 5 μm. Example 5

[0030] TH-904 and BYK-190 from Shandong Taihe Technology Co., Ltd., 200nm spherical silica particles from Anhui Fangxing Technology, LLZO inorganic solid electrolyte from Ningbo Fengli New Energy LLZO-G3-300; ZL057 high carbon alcohol defoamer from Yiwu Zhongli Industry and Trade; GY-738 coconut oil diethanolamide from Shanghai Yuanye Biotechnology Co., Ltd.; 17-96 (L) polyvinyl alcohol from Wanwei High-tech Materials; 8000rpm AIR-10S Shanghai Ouhe high-speed agitator; 8501 diaphragm coating adhesive.

[0031] Step 1: Preparation of functional coating materials for coating inorganic particles: By weight, 10 parts of silica particles were added to 20 parts of deionized water, and the particles were dispersed using an AIR-10S high-speed stirrer for 1 hour to disperse the particles evenly. 2 parts of Alcosperse 602N dispersant were added and stirred for 20 minutes to allow the dispersant to be fully adsorbed on the surface of the inorganic particles. In another container, a certain amount of deionized water was heated to 80°C. 15 parts of polyvinyl alcohol were slowly added, stirring while adding to prevent polyvinyl alcohol from agglomerating, and the temperature was continued to be stirred and maintained at 80°C to completely dissolve the polyvinyl alcohol to form a transparent 25wt% polyvinyl alcohol solution. The stirring and dissolving time was 3 hours and the stirring speed was 200rpm; the pretreated inorganic particle slurry was added to the reactor. Turn on the stirrer and slowly add the obtained polyvinyl alcohol solution. The temperature of the reactor was raised to 70°C and stirred to coat the surface of the inorganic particles with polyvinyl alcohol. The coating time was 5 hours. The average particle size of the polyvinyl alcohol-coated inorganic particles is 0.9 μm; when the coating time reaches 90% of the total coating time, that is, after 4.5 hours of coating, 10 parts of high-carbon alcohol defoamer and 10 parts of coconut diethanolamide thickener auxiliary are added and stirred evenly to finally prepare a functional coating slurry of polyvinyl alcohol-coated inorganic particles.

[0032] Step 2: Preparation of first coating slurry: By weight, 30 parts of functional coating slurry, 10 parts of binder, and 40 parts of water were stirred evenly to obtain a first coating slurry. The functional coating slurry of the polyvinyl alcohol-coated inorganic particles was coated on one side of the base film. After baking at 80°C for 1 hour, a coating was formed, and the composite diaphragm was rolled up; the coating thickness was 5 μm.

[0033] Step 3: Preparation of the second coating slurry: By weight, 1 part of Alcosperse 602N dispersant was added to 8 parts of deionized water, and stirred thoroughly for 30 minutes. 15 parts of LLZO inorganic solid electrolyte were added and stirred for 60 minutes to obtain a water dispersion. 8 parts of coconut oil diethanolamide were added for thickening, and 50 parts of deionized water dispersion were added and stirred for 2 hours. 3 parts of binder were added and stirred for 2 hours. Finally, an inorganic solid electrolyte slurry was prepared. After baking at 80°C for 1 hour, a coating was formed, and the composite diaphragm of a semi-solid battery was rolled up. The coating thickness was 10 μm.

[0034] Comparative Example 1 The method is the same as that of Example 1, except that no polyvinyl alcohol raw material is added to the first coating slurry.

[0035] Comparative Example 2 The method is the same as that of Example 1, except that no inorganic solid electrolyte raw material is added to the second coating.

[0036] Comparative Example 3 The same method as in Example 1, except that no spherical silica particles were added to the first coating.

[0037] The results of tensile strength, puncture strength, closure temperature, membrane rupture temperature and porosity of the semi-solid battery composite separators prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1 below.

[0038] Table 1 Test results of semi-solid battery composite diaphragms of Examples 1 to 3 and Comparative Examples 1 to 3

[0039] According to the table data, the semi-solid composite battery diaphragm solution provided by the present invention significantly improves the ionic conductivity of the diaphragm without affecting the porosity and mechanical strength. Compared with the prior art, the PVA coating not only enhances the mechanical strength and toughness of the diaphragm, but also improves the ionic conductivity and improves the interface contact with the electrode; at the same time, the inorganic nanoparticles provide a good conductive channel, which helps the rapid migration of lithium ions. In addition, LLZO, as an inorganic solid electrolyte, has high chemical stability and thermal stability. Compared with traditional liquid electrolytes, it is not easy to burn and can significantly reduce the risk of thermal runaway of the battery under overcharge, over-discharge or high temperature environment. The composite diaphragms in Examples 1-3 perform well in mechanical properties and porosity, among which the ionic conductivity of Example 1 is significantly higher than that of the other two groups and Comparative Examples 1-3. At the same time, the thickness of the diaphragm of Example 1 is thin, which meets the actual application requirements. On the whole, Example 1 performs well in both performance and processing difficulty, becoming the most ideal solution in the present invention.

[0040] The above is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. All equivalent changes and modifications made according to the content of the present invention are included in the patent scope of the present invention.

[0041] Note: Refer to GB / T36363-2018 Polyolefin separators for lithium-ion batteries.

Claims

1. A semi-solid battery composite diaphragm, characterized in that: The semi-solid battery composite diaphragm comprises a thermoplastic resin porous base film and a first coating and a second coating respectively coated on the upper and lower surfaces of the thermoplastic resin porous base film; the preparation method of the semi-solid battery composite diaphragm comprises the following steps: coating the upper and lower surfaces of the thermoplastic resin porous base film with a first coating slurry containing a functional coating slurry and a second coating slurry containing an inorganic solid electrolyte on both sides of the upper and lower surfaces of the thermoplastic resin porous base film, baking to form the first coating and the second coating, and rolling up to obtain the composite diaphragm.

2. A method for preparing a semi-solid battery composite diaphragm, for preparing the semi-solid battery composite diaphragm according to claim 1, characterized in that: The first coating slurry is prepared by the following method: by weight, 20 to 30 parts of functional coating slurry, 5 to 10 parts of binder, and 30 to 40 parts of water are stirred uniformly to obtain the first coating slurry; the functional coating slurry comprises the following components in parts by weight: 5 to 10 parts of silica particles, 5 to 20 parts of polyvinyl alcohol, 10 to 15 parts of thickener, 8 to 10 parts of defoamer, 2 to 4 parts of dispersant and 65 parts of deionized water; The second coating slurry is prepared by the following method: 1 to 2 parts of dispersant are added to 8 to 10 parts of deionized water, and the mixture is stirred thoroughly for 30 minutes; 15 to 20 parts of inorganic solid electrolyte are added, and the mixture is stirred for 40 to 60 minutes to obtain a water dispersion; 8 to 10 parts of thickener are added for thickening, and 50 parts of deionized water are added to obtain a deionized water dispersion, which is stirred for 2 hours; 3 parts of binder are added, and the mixture is stirred for 2 hours to finally prepare an inorganic solid electrolyte slurry, i.e., the second coating slurry.

3. The method for preparing a semi-solid battery composite diaphragm according to claim 2, characterized in that: The preparation method of the functional coating slurry is as follows: (1) adding silica particles into deionized water, dispersing them using a high-speed stirrer, stirring until the particles are evenly dispersed, adding a dispersant and continuing to stir until stable, to obtain a pretreated inorganic particle slurry; (2) Adding polyvinyl alcohol to deionized water at a constant temperature of 80° C. while stirring to obtain a polyvinyl alcohol solution; (3) Add the pretreated inorganic particle slurry into the reactor, turn on the stirrer, and slowly add the polyvinyl alcohol solution. After the addition is completed, raise the temperature to 70°C, keep stirring, and control the coating reaction time to 5 hours; (4) Before the coating reaction is completed, add a defoamer and a thickener, stir evenly, and obtain a functional coating slurry.

4. The method for preparing a semi-solid battery composite diaphragm according to claim 2, characterized in that: The inorganic solid electrolyte is lithium lanthanum zirconium oxide.

5. The method for preparing a semi-solid battery composite diaphragm according to claim 2, characterized in that: The dispersant is one of TH-904, BYK-190 and sodium polyacrylate.

6. The method for preparing a semi-solid battery composite diaphragm according to claim 2, characterized in that: The thickener is coconut diethanolamide.

7. The method for preparing a semi-solid battery composite diaphragm according to claim 2, characterized in that: The thermoplastic resin porous base film is a PE diaphragm prepared from polyethylene raw materials.

8. The method for preparing a semi-solid battery composite diaphragm according to claim 2, characterized in that: The composite diaphragm has a thickness of 24 to 34 μm.

9. The method for preparing a semi-solid battery composite diaphragm according to claim 2, characterized in that: The baking temperature is 60-80°C and the baking time is 1-2 hours.

Citation Information

Patent Citations

  • Isolation membrane for lithium ion secondary battery

    CN104868084A

  • Preparation method of ceramic coating diaphragm, diaphragm and ceramic coating slurry

    CN111116963A

  • Composite diaphragm for semi-solid lithium battery and preparation method of composite diaphragm

    CN114156595A

  • Layered oxide electrolyte semi-solid diaphragm as well as preparation method and application thereof

    CN117039344A

  • Ceramic microsphere, diaphragm including ceramic microsphere and lithium ion battery including diaphragm

    US20220278421A1